Meta-análise de parâmetros genéticos relacionados ao consumo alimentar residual e a suas características componentes em bovinos - Del Claro, Ana Cecília; Mercadante, Maria Eugênia Zerlotti; Vasconcelos Silva II, Josineudson Augusto [UNESP] (FapUNIFESP (SciELO), 2012)
The objective of this work was to estimate, by meta-analysis, the heritability (h 2) and the genetic (r g) and phenotypic (r f) correlations of residual feed intake (RFI), and of its component traits in beef cattle from 19 breeds or genetic groups. Twenty-two scientific papers published from 1963 to 2011, from eight countries, totaling 52,637 cattle of ages from 28 days up to slaughter, were evaluated. The estimates of RFI, dry matter intake (DMI), average daily gain (ADG) and metabolic weight (BW 0.75) were weighted by the inverse of sample variance. The variation between studies of h 2 for each trait was analyzed by weighted least squares. The effects of sex, country and breed were significant for h 2 of RFI, explaining 67% of variation between studies. For DMI, country and breed effects were significant and explained 96% of variation. Pooled estimates of h 2 were: 0.255±0.008, 0.278±0.012, 0.321±0.015, and 0.397±0.032 for RFI, DMI, ADG and BW 0.75, respectively. Pooled estimates of genetic and phenotypic correlations were low between RFI and ADG and between RFI and BW 0.75 (from -0.021±0.034 to 0.025±0.035), and moderate between RFI and DMI (0.636±0.035 and 0.698±0.041) and between DMI, ADG and BW 0.75 (0.441±0.062 to 0.688±0.032). The trait RFI has lower heritability estimates than its components.
Meta-analysis of genetic parameter estimates of residual feed intake and of its component traits in cattle
Keywords: Dry matter intake; Feed efficiency; Genetic correlation; Heritability; Metabolic weight; Pooled estimates